2015
DOI: 10.12983/ijsres-2015-p0009-0015
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Butt Waste and Its Effective Utilization towards Larvicidal Activity of Mosquito

Abstract: Abstract.Mosquito Bourne disease is a major threat to public health in urban areas. Synthetic insecticides often results adverse environmental effects. The present paper deals with the control of mosquito larvae using cigarette butts (CBs), an waste product. Cigatette butts are thrown everywhere, where it may cause severe problem as it contains several toxic materials. These toxic materials can cause harm to our environment. It is also reported in literature that in the water bodies where the cigarette butts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…pipiens larvae, which had been exposed to all the plant waste extracts in our investigation after 24 and 48 h. Several researchers recently evaluated cigarette butts, which are the unburned part of cigarette tobacco, along with a cigarette filter. The authors confirmed the toxicity of cigarette butts in killing mosquito larvae at a high rate, especially with increasing amounts of cigarette butts [32][33][34][35] . However, the effect of cigarette filters has not been studied; although they do not contain tobacco of any two flavors, burnt tobacco passes through them in addition to other components added to tobacco, which increases our belief that the cigarette filter contains toxic compounds that may reach or exceed the cigarette butts.…”
Section: Discussionmentioning
confidence: 62%
“…pipiens larvae, which had been exposed to all the plant waste extracts in our investigation after 24 and 48 h. Several researchers recently evaluated cigarette butts, which are the unburned part of cigarette tobacco, along with a cigarette filter. The authors confirmed the toxicity of cigarette butts in killing mosquito larvae at a high rate, especially with increasing amounts of cigarette butts [32][33][34][35] . However, the effect of cigarette filters has not been studied; although they do not contain tobacco of any two flavors, burnt tobacco passes through them in addition to other components added to tobacco, which increases our belief that the cigarette filter contains toxic compounds that may reach or exceed the cigarette butts.…”
Section: Discussionmentioning
confidence: 62%
“…This research suggests that CBs waste, which is abundant and hazardous, has the potential to be converted into a low-cost and environment-friendly source for the production of insecticides and antimalarials. However, additional research is needed to examine the effects of CBs on non-target organisms and humans [ 83 ].…”
Section: Recycling Strategies For Litter Cbs Managementmentioning
confidence: 99%